The Effect of Glucocorticoids on Bone Profile in Pediatric Acute Lymphoblastic Leukemia - Pramulya Prajogo; Bidasari Lubis; Siska Mayasari Lubis; Isti Ilmiati Fujiati; Tiangsa Sembiring; Hafaz Zakky Abdillah (Indonesian Journal of Global Health Research, 2026)
Glucocorticoids are essential in treating acute lymphoblastic leukemia (ALL) but may disrupt bone metabolism, affecting calcium, magnesium, phosphate, and alkaline phosphatase levels. This cross-sectional study enrolled 30 children ≤18 years with ALL at Adam Malik Hospital, Medan, during April–May 2025 using consecutive sampling. All had received at least one week of glucocorticoid therapy and had complete bone profile data. Data were obtained from medical records and laboratory tests. Associations were analyzed using Spearman’s correlation, Mann-Whitney test, and multiple linear regression. Most patients were male (53.3%) and classified as high-risk (60%), with 60% receiving dexamethasone for a median of 7 weeks. Calcium, phosphate, and alkaline phosphatase levels were generally within the normal range, but 50% of patients developed hypermagnesemia. Magnesium levels were significantly associated with the type of glucocorticoid (p=0.010), treatment duration (p=0.014), and age at diagnosis (p=0.006). No significant associations were found between glucocorticoid duration and calcium, phosphate, or alkaline phosphatase levels. Magnesium levels are influenced by glucocorticoid type, treatment duration, and age at diagnosis. Further studies with larger samples and additional biomarkers are needed to comprehensively understand the effects of glucocorticoids on the bone profile of children.